Complaint Strategies by Indonesian with Special Preference to Makassarese - Pratiwi Bahar (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This research aims to elaborate the kind of complaint strategies do Indonesian with Special Preference to Makassarese employ. This research study adopts DCT (Discourse Completion Task) as the research instrument for collecting data. DCT is a form of questionnaire describing some natural situations to which the respondents are expected to react making complaints. The data for this study taken from 30 native speakers of Indonesian especially Makassarese. Subjects are asked to participate in the study in person by the researcher. The subjects are provided with a survey packet comprised of the Informed Consent, the Demographic Survey, and the DCT. Subjects are asked to complete the Informed Consent. In analyzing the data, the researcher makes a table of responses from all the respondents in each situation. And then, the data of this research are analyzed based on the compilation of strategy from six linguists such as Giddens (1981), Olstain & Weinbach (1993), Boxer (1993), Trosborg (1995), Murphy & Neu (1996), and Rinnert & Nogami (2006). By this compilation of strategy, the researcher identifies the strategy applied by the participant in complaining. The analysis shows that the kind of complaint strategies do Indonesian especially Makassarese in complaining are complaint, criticism, explanation of purpose, candidate solution, sarcasm, threat, apology, asking for responsibility, expressing disappointment, opener, justification, preaching, closing and satire. By doing a research about complaining behavior of Indonesian, the researcher suggests in this study that is the addition to the notion of classification of complaint strategy developed by the linguists based on the phenomena found in the research. The strategy is added up to this compilation is satire. Satire is a humorous way of criticizing people or ideas to show that they have faults or are wrong, or a piece of writing or a play that uses this style.